PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT UNTUK MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS V SD NEGERI 018 UKUI 1 KECAMATAN UKUI - Narko ' (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This research was motivated by lack of civics student learning outcomes. Low learningoutcomes are caused by: (a) students do not really follow civics and they talk to each othersawaktu teacher explains the lesson; (B) students are not active in learning; (C) if the teacherasking questions, very few students who answered; and (d) very few students were askedabout the learning that has not been understood, in addition to the learning activities in theclassroom dominated by teachers and children are much more powerful. This study aims toimprove learning outcomes civics through cooperative learning model NHT. This study is aclass action, which was conducted in 018 primary schools Ukui 1 Subdistrict Ukui. This studyfocused on students' learning outcomes data civics. Based on the results of the study revealedthat the civic education learning outcomes of students has increased. This is evidenced by:Improved student learning outcomes at the preliminary data the number of students who passare 15 students (50%), increasing in the first cycle increased to 26 students (87%) and incycle II further increased up to 27 students (90 %).